The Silurian greening of planet Earth - Edwards, Dianne (2010)
Comparative studies on spores and megafossils of early land plants in Silurian times will be reviewed in an attempt to reconstruct the pioneering phases of terrestrial vegetation on both regional and global scales. Traditionally the advent and diversification of vascular plants have dominated such studies. The recent discoveries of in situ nontrilete spores (viz. cryptospores in the form of dyads and tetrads) and subsequent ultrastructural studies permit more informed speculation on the nature and significance of the earliest embryophytes which are generally accepted as related to bryophytes.